On the Gevrey regularity for weakly hyperbolic equations with space-time degeneration of Oleinik type - R. MANFRIN; F. TONIN (Rendiconti di Matematica e delle Sue Applicazioni, 1996)
We are concerned with the problem of global Gevrey regularity of solutions of quasi-linear weakly hyperbolic equations. Assuming a Oleinik’s type condition on the nonlinear term, we establish a suitable energy estimate which permits to prove the propagation of the Gevrey regularity of the C2 solutions.